COMPARISON OF QUALITY OF LIFE BETWEEN COMBINED THERAPY AND ADDITIONAL CORTICOSTEROID INJECTIONS IN ADVANCED KNEE OSTEOARTHRITIS AT SITI KHODIJAH HOSPITAL - Hefni, Muhammad Naufaldi; Wirashada, Brilliant Citra; Puspita, Eka Ari (Universitas Muhammadiyah Surakarta, 2026)
Background: Knee osteoarthritis (OA) causes pain, stiffness, and functional decline, reducing quality of life. Objective: This study compared the quality of life of advanced knee OA patients (Kellgren–Lawrence grade 3–4) receiving the combination of pharmacological and physiotherapy treatment alone and those who received the same combination with the addition of intra-articular corticosteroid injections. Methods: This research is a quantitative analytic observational study using cross-sectional collecting method involving 44 patients diagnosed in the year of 2023 with advanced knee OA at Siti Khodijah Sidoarjo Hospital. Data were collected through medical records and WOMAC questionnaires, and analyzed using the Mann–Whitney U test and mean rank comparison between treatment groups. Results showed that the injection group had significantly lower WOMAC Scores (19.2 ± 14.0) compared to the non-injection group (35.07 ± 8.6) and p-value of 0.000 (p < 0.05). Conclusion: The addition of intra-articular corticosteroid injections significantly improves the quality of life in patients with advanced knee OA.